Decreased Netrin-1 in Mild Cognitive Impairment and Alzheimer’s Disease Patients - Ju, Ting; Sun, Lina; Fan, Yuwei; Wang, Tianhang; Liu, Yanchen; Liu, Dan; Liu, Tianyi; Zhao, Chang; Wang, Wenxin; Chi, Lijun (Frontiers in Aging Neuroscience, 2022)
Background and objective: Inflammatory mediators are closely associated with the pathogenesis of Alzheimer’s disease (AD) and mild cognitive impairment (MCI). Netrin-1 is an axon guidance protein and despite its capacity to function as a neuroimmune guidance signal, its role in AD or MCI is poorly understood. In addition, the association among netrin-1, cognitive impairment and serum inflammatory cytokines such as interleukin-17 (IL-17) and tumor necrosis (TNF-α) remains unclear. The aim of this study was to determine serum levels of IL-17, TNF-α and netrin-1in a cohort of AD and MCI patients, and to study the relationship between these cytokines and cognitive status, as well as to assess the possible relationships between netrin-1 levels and inflammatory molecules. Methods: Serum concentrations of netrin-1, TNF-α and IL-17 were determined in 20 AD patients, 22 MCI patients and 22 healthy controls using an enzyme-linked immunosorbent assay (ELISA). In addition, neuropsychological evaluations and psychometric assessments were performed in all subjects. Results: Serum netrin-1 levels were decreased in AD and MCI patients and were positively correlated with Mini Mental State Examination (MMSE) scores. In contrast, serum TNF-α and IL-17 levels were elevated in AD and MCI cohorts and negatively correlated with MMSE scores. Serum netrin-1 levels were inversely related with TNF-α and IL-17 levels in AD, but not MCI, patients. Conclusion: Based on the findings reported here, netrin-1 may serve as a marker for the early recognition of dementia and predict cognitive impairment.